Population Pharmacokinetics and Pharmacodynamics of Lampalizumab Administered Intravitreally to Patients With Geographic Atrophy. (8th October 2015) - Le, KN; Gibiansky, L; van Lookeren Campagne, M; Good, J; Davancaze, T; Loyet, KM; Morimoto, A; Strauss, EC; Jin, JY
Abstract : Intravitreally administered lampalizumab is an investigational complement inhibitor directed against complement factor D (CFD) for the treatment of geographic atrophy (GA) secondary to age‐related macular degeneration. We sought to develop an integrated ocular and systemic pharmacokinetic/pharmacodynamic model for lampalizumab in patients with GA using the data from the clinical phase I and II studies. The kinetics of lampalizumab and CFD disposition were well described by the combined ocular/serum target‐mediated drug disposition model using a quasi‐steady‐state approximation. This model takes into account the drug, target, and drug–target complex clearance, their transfer rates between ocular and serum compartments, and turnover kinetics of CFD. The constructed model provided a prediction of target occupancy in ocular tissues and supported that the two dosing regimens (10 mg q4w and 10 mg q6w) selected for the phase III studies are expected to be efficacious and able to achieve near‐complete target engagement in the vitreous humor.